Dermal exposure and risk assessment of tebuconazole applicators in vineyards - Mandic-Rajcevic, Stefan; Rubino, Federico Maria; Vianello, Giorgio; Fugnoli, Lorenzo; Polledri, Elisa; Mercadante, Rosa; Moretto, Angelo; Fustinoni, Silvia; Colosio, Claudio (La Medicina del Lavoro, 2015)
Introduction: Models used in the pre-marketing evaluation do not cover all work scenarios and may over- or underestimate exposure. Objectives: Uncertainties present in the extrapolation from pre-marketing to the post-marketing warrant exposure and risk assessment in real-life working conditions. Methods: Seven vineyard pesticide applicators were followed for a total of 12 work-days. A data collection sheet was developed specifically for this study. Workers’ body exposure, hands, and head exposure were measured. Tebuconazole was analyzed using LC-MS/MS. Results: Median potential and actual body exposures were 22.41 mg/kg and 0.49 mg/kg of active substance applied, respectively. The median protection factor provided by the coverall was 98% (range: 90-99%). Hand exposure was responsible for 61% of total actual exposure, and was reduced by more than 50% in workers using gloves. The German Model underestimated the exposure in one work-day, and grossly overestimated it in 3 work-days. Conclusions: High levels of potential body exposure were efficiently controlled by the cotton coverall. Use of personal protective devices, especially chemically-resistant gloves and head cover is the main determinant of skin protection. Field studies on pesticide exposure in real-life conditions and development of methods and tools for easier risk assessment are necessary to complement and confirm the risk assessment done in the authorization process.